Pengaruh Pergaulan terhadap Motivasi Belajar Mahasiswa PAI Angkatan 2020 Universitas Neegri Padang - Naputra, Danil; Sulaiman, Sulaiman (ISLAMIKA, 2024)
Getting along should be a relationship between fellow human beings. Human to another human being is established through a time-cycle process that is relatip long time then influenced and influenced in increasing learning motivation, it is necessary driving force that stimulates interest in learning and allows for continuous learning. Continuous learning. Through learning motivation can be interpreted as a reciprocal force through one's internal and external self when carrying out the learning process. When carrying out the learning process. The study aims to determine the effect of socialization on the learning motivation of UNP 2020 PAI students. Quantitative research through the type of correlation and in the organization through statistical analysis techniques descriptive statistical analysis technique. Data collection presents primary data as well as validity and reliability tests. Through determining the sample of 2020 PAI students as many as 60 people. The whole data is allocated based on instrument questionnaires from the socialization and learning motivation variables. Overall results of the data analysis were calculated and tested through statistical calculations and correlation of the mean found using SPSS software. The data results attach a positive significant vibes of association to learning motivation 59.3%. The results show that overall socialization has a significant influence on learning motivation, meaning that learning motivation is influenced by socialization. is influenced by socialization. Researchers recommend that be smart in choose socialization.